Socioeconomic Determinants of Stigmatization and HIV Testing in Lesotho - Corno, Lucia (Taylor and Francis, 2013)
HIV/AIDS stigmatizing attitudes and their consequences on preventative behaviors are among the most poorly understood aspects of the AIDS epidemic. This paper analyzes the socioeconomic determinants of discriminating attitudes toward people living with HIV and their implications on the likelihood of HIV testing. These effects are tested using the 2004 and 2009 Demographic and Health Surveys conducted in Lesotho, where HIV/AIDS is a pervasive problem. We find that HIV/AIDS stigmatizing attitudes are negatively associated with education and wealth and positively correlated with Catholic religion for women and traditional circumcision for men. The analysis also shows a negative association between stigmatizing beliefs and the probability of being tested for HIV.